Grounded Theory through the lenses of interpretation and translation - Maria Mouratidou; Mark Crowder; Helen Scott (Grounded Theory Review: An International Journal, 2020)
This paper explores interpretation and translation issues that arose during a grounded theory study of the Greek health sector. It highlights problems that were encountered when working in two languages and demonstrates how these were overcome. This is important because